2018
DOI: 10.36076/ppj.2018.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Posterolateral Fusion Versus Posterior Lumbar Interbody Fusion in Patients with Lumbar Spinal Stenosis and Degenerative Instability

Abstract: Background: Degenerative lumbar spine disease can lead to lumbar spine instability. Lumbar spine instability is defined as an abnormal response to applied loads characterized kinematically by abnormal movement in the motion segment beyond normal constraints. Patients with lumbar spinal stenosis (LSS) typically present with low back pain (LBP), cramping, cauda equine syndrome, and signs of nerve root compression associated by weakness, numbness and tingling in their legs that are worsened with standing and walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 70 publications
(142 reference statements)
0
28
1
1
Order By: Relevance
“…A negative correlation between PT and PLBP in spondylolisthesis patients has also been found, indicating that lumbar degeneration accompanies sagittal balance deterioration [9]. For most DS patients, PLIF can dramatically improve sagittal balance via the fixation of pedicle screws and distraction of the inserted cage [10]. However, few studies have been published about correlation between spinopelvic sagittal balance and clinical outcomes, especially the impact of spinopelvic sagittal balance on PLBP.…”
Section: Introductionmentioning
confidence: 99%
“…A negative correlation between PT and PLBP in spondylolisthesis patients has also been found, indicating that lumbar degeneration accompanies sagittal balance deterioration [9]. For most DS patients, PLIF can dramatically improve sagittal balance via the fixation of pedicle screws and distraction of the inserted cage [10]. However, few studies have been published about correlation between spinopelvic sagittal balance and clinical outcomes, especially the impact of spinopelvic sagittal balance on PLBP.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent findings suggest that decompression and posterior fusion and using methylene blue on the soft tissue around fusion site during spinal surgeries are effective surgical methods which are associated with satisfying clinical results in terms of improvement of postoperative low back pain (LBP), radicular pain, and quality of life (QOL) (14-16). Our 2018 randomized prospective controlled clinical study (17), which has been recently accepted for publication in PAIN PHYSICIAN, compared the clinical outcomes of posterolateral fusion (PLF) with posterior lumbar interbody fusion (PLIF) with posterior instrumentation after lumbar decompression surgery for lumbar spinal stenosis (LSS) and degenerative lumbar spine instability. Our findings showed that compared with PLIF, PLF with posterior instrumentation in patients with LSS and degenerative lumbar spine instability provides better clinical outcomes and improvement in the LBP, radicular pain, and functional QOL (Table 1).…”
Section: )) No Significant Difference Was Found In the Parameters mentioning
confidence: 99%
“…Their findings are important as they provide a better cure for back pain without predisposing patients to future spinal problems. Meanwhile, however, the fact that there are many studies in the literature which show that posterolateral fusion (PLF) provides better clinical outcomes and more improvement in low back pain than PLIF [2,3] raises this question that if according to Su et al [1], ISOBAR device use is superior to standard approaches such as PLIF, then we can take a step forward and hypothesize that ISOBAR device may also be more effective than PLF, but this should be investigated. Regarding different findings of various studies, we cannot reach a consensus on the superiority of ISOBAR devices over PLF.…”
mentioning
confidence: 99%
“…One of the major issues after lumbar spinal fusion is the development of adjacent segment disease (ASD), resulting in clinical symptoms and detectable imaging study abnormalities [4]. Degeneration that develops at mobile segments above or below a fused spinal segment is known as ASD [2]. The increase of adjacent segment compensatory activity after rigid internal fixation is one of the most important causes of adjacent segment degeneration [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation